Show Me What You Know. (7th January 2015) - Young, Teresa; Morgan, Ashley
Abstract Early childhood teachers promote literacy learning through intentional instructional practices and the establishment of classroom environments that encourage and support the work, interest, and curiosity of young learners. They provide opportunities for children to engage with their teacher and peers and consider this an important component of literacy learning. Moreover, teachers design visually pleasing environments that support students' prior knowledge and experiences. The project approach to learning integrates all of the basic elements of literacy learning while respecting the natural inquisitive nature of children and their need to construct their own learning as they interact within their classroom environment, peers, and teachers. In this article, we share a snapshot of how one kindergarten teacher incorporated elements of the project approach within her classroom in the hopes that other teachers will feel inspired to try aspects of this method of teaching in their own classrooms.